A model for a sensory study of soft drinks in the domestic market - Amaro Baldeón, Roberto (1999)
A model to measure objectively the probability preferably having the public for a soft drink, the variable to be measured is sensory, ie is a subjective variable, in our case the flavor is presented in preente thesis, for Kola Real, Coca Cola and Pepsi Cola: organoleptic study, three sodas were selected. The advantage of the model presented is grouped qye soda in pairs, each pair consisting of a group of respondents was presented which showed individual preference or indifference sodas presented in par.